2015
DOI: 10.1371/journal.pone.0132660
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetics and Antimicrobial Susceptibility of Canine Campylobacter Isolates Collected before and after a Raw Feeding Experiment

Abstract: In recent years, increasing numbers of consumers have become interested in feeding raw food for their pet dogs as opposed to commercial dry food, in the belief of health advantages. However, raw meat and internal organs, possibly contaminated by pathogens such as Campylobacter spp., may pose a risk of transmission of zoonoses to the pet owners. Campylobacter jejuni is the leading cause of bacterial gastroenteritis in humans but C. upsaliensis has also been associated with human disease. In this study we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 58 publications
0
8
1
1
Order By: Relevance
“…12.6%. This result stood in opposition to our earlier studies [ 1 , 20 ] and research conducted by other authors [ 5 , 21 ]. Chaban et al [ 22 ] analysed a group ( n = 70) of healthy dogs and found bacteria of the Campylobacter genus in 58% of the samples.…”
Section: Discussioncontrasting
confidence: 99%
“…12.6%. This result stood in opposition to our earlier studies [ 1 , 20 ] and research conducted by other authors [ 5 , 21 ]. Chaban et al [ 22 ] analysed a group ( n = 70) of healthy dogs and found bacteria of the Campylobacter genus in 58% of the samples.…”
Section: Discussioncontrasting
confidence: 99%
“…20 28-33 In addition, Listeria greyii has been found in a dry pet food. 20 One study reported no diference in the carriage of Campylobacter species in dogs fed either a raw or a dry diet, 34 and one study found Salmonella species in three dogs that had not been given raw food of any kind and found no Salmonella species in dogs fed raw foods (n=24). 35 In addition to Salmonella, diferent kinds of mycotoxins [36][37][38][39] have been found in heat-treated pet foods, causing health problems to the pets themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Serotyping was done with commercial antisera (Denka Seikan, Japan). The presence of Campylobacter was studied by plating (1 g feces/1 mL 0.9% saline) on modified charcoal cefoperazone deoxycholate agar (mCCDA) with cefoperazone and amphotericin (Oxoid, Basingstoke, UK) and identification was done by gram staining and PCR according to Olkkola et al [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…These pathogens are widespread in nature and found in the gastrointestinal tract of wild and domestic mammals and birds. They have also been reported in dogs and cats with and without diarrhea [ 14 , 16 , 28 ]. However, the reported prevalence rates vary highly between the studies ( Table 1 ).…”
Section: Introductionmentioning
confidence: 97%